Contribution of School Committees in the Operation of Education in Junior High School 3 Sigli - Ismail; Salahuddin (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
School committees are formed as advisory bodies (Advisory Agency) and also as supporting (supporting agencies) as well as controlling (controlling agency) in the context of educational transparency, as well as mediators between the government (executive) and the community in the education unit. Based on empirical data, the school committee of Junior High School 3 Sigli has not shown an optimal contribution in the administration of education, especially in the teaching and learning process. School committees contribute more dominantly when there is education assistance provided by the government. The purpose of this research is to analyze the contribution of the school committee as an educational consideration body, as an educational support body and to analyze the contribution of the school committee as an education control body at Junior High School 3 Sigli. The approach used in this research is qualitative, while data collection techniques are carried out through observation, interviews, focus group discussion (FGD) and documentation. The results showed that the contribution of the school committee as an educational consideration body at the Junior High School 3 Sigli had not gone perfectly, both with regard to planners, executors and managers. While the contribution of the school committee with regard to supporting bodies as government partners has also not gone well, because what is highlighted by the school committee is only when there is financial assistance. While the contribution of the school committee as a partner with the community and also a partner with the school is quite good, so is the contribution of the school committee as an education control body. The conclusion of the study shows that the contribution of Junior High School 3 Sigli committee can improve the quality of education, although it is related to the educational consideration body its contribution is not yet perfect, but with the contribution of the school committee as a support body and education control body, it has a positive impact on the smooth and comfortable teaching and learning process.